Role of governance index, democracy, industrialization, and urbanization on environmental sustainability of BRICS countries: A novel PMG-ARDL approach - Md Atik Hasan; Liton Chandra Voumik; Ajharul Islam Mozumder; Miguel Angel Esquivias; Leslie Verteramo-Chiu; Mihir Kumar Das (Social Sciences and Humanities Open)
This research examines the environmental sustainability dynamics of BRICS countries from 1996 to 2022, focusing on governance, democracy, industrialization, and urbanization's impact on the Load Capacity Factor (LCF). Using the Panel Mean Group Autoregressive Distributed Lag (PMG-ARDL) model, the study validates findings with fully modified OLS (FMOLS) and Common Correlated Effects (CCR) methodologies. Results indicate a positive, statistically significant relationship between the governance index and LCF, suggesting effective governance enhances environmental sustainability. In contrast, democracy, industrialization, and urbanization negatively affect LCF, implying these factors strain resources and hinder sustainability. Strengthening governance and sustainable development policies can mitigate these adverse effects, promoting a resilient future for BRICS countries.